(untitled) (Universal International Scientific Journal, 2026)
Memory plays a central role in the process of learning a foreign language, particularly in English language teaching (ELT), where learners are required to acquire, store, retain, and retrieve large amounts of linguistic information. This article examines the theoretical foundations of memory from the perspectives of cognitive psychology and applied linguistics and explores their relevance to English language teaching. The study analyzes key memory models, including short-term memory, long-term memory, and working memory, and discusses their impact on vocabulary acquisition, grammar learning, and speaking fluency. Special attention is given to memory-related processes such as encoding, retention, and retrieval, which significantly influence language learning outcomes. The article also highlights the pedagogical implications of memory theories for classroom practice, emphasizing memory-based teaching strategies that enhance learners’ cognitive engagement and long-term language retention.